Avaliação de formação em letramento destinada a educadores, mães e jovens das comunidades rurais de Parati - Leite, Rita Carmona Moreira (2009)
This research consists of an evaluation of lhe formation in literacy aimed for teachers, youngsters and mothers from lhe rural communities of Parati city, executed and managed by two NGOs in partnership with lhe Municipal Department of Education. The evaluation applied followed a qualitative approach and utilized as source of data documents created by lhe formation team, questionnaires applied to lhe participating teachers, as well as an interview with someone responsible for managing and overseeing lhe formation itself. The evaluation of this formation process intends to contribute of lhe creation of more contextualized curriculums and a better integration between school, family and community